Antifungal activity of methanolic extracts of Jacquinia macrocarpa and Krameria erecta on the growth of Fusarium verticillioides and effect on fumonisin production - Fabiola Fimbres-López (Revista Mexicana de Micología, 2016)
Some medicinal plants have been studied on phytopathogenic fungi for their antifungal activity. For this reason the goal of this study was to evaluate methanolic extract of Jacquinia macrocarpa and Krameria erecta on radial growth, spore germination, biomass production of Fusarium verticillioides. Methanolic extract of J. macrocarpa which caused the best results was sequentially partitioned with hexane, ethyl acetate and n-butanol. Only the butanolic fraction was active. It delayed the spore germination and the colony growth changed from radial to apical, which is a way to express it is under pressure due to chemicals present in the fraction. Fumonisin production was not affected by the extract. We conclude that J. macrocarpa methanolic extract and its butanolic fraction are capable to delay the radial growth of F. verticillioides and the kinetic of spore germination and do not affect fumonisin production.